The effects of N‐ethyl‐N′‐methyl imidazolium chloride on the solubility, stability and aggregation of tc‐rPA. (19th February 2014) - Tischer, Alexander; Pultke, Heiko; Topf, Andrea; Auton, Matthew; Lange, Christian; Lilie, Hauke
<x xml:space="preserve">Abstract</x> The ionic liquid N‐ethyl‐N′‐methyl imidazolium chloride (EMIMCl) has been described as being very efficient in promoting refolding of the recombinant plasminogen activator rPA. Our study reveals that molar concentrations of EMIMCl increase the solubility of native and unfolded proteins due to favorable interactions with amino acid side chains rather than favorably interacting with the peptide backbone. This delicate balance of favorable interactions with side chains and unfavorable interactions with the peptide backbone provides a molecular explanation of how EMIMCl suppresses protein aggregation and simultaneously promotes refolding. By contrast, high concentrations of EMIMCl denature proteins because of a reduced water content and strong favorable interactions with amino acid side chains. This denatured species is not soluble and aggregates because, in contrast to the classical denaturants, guanidine hydrochloride and urea, EMIMCl does not solubilize the peptide backbone. Structured digital abstract PNP and PNPbind by molecular sieving (1, 2, 3, 4)